(untitled) (The Planet, 2024)
Introduction: A fracture shaft of the femur refers to a break or crack that occurs along the long, cylindrical portion of the femur bone in the thigh. Surgical intervention is often necessary for displaced or unstable fractures. Two reduction methods, open and closed nailing are used for the fixation of femoral shaft fractures. Objective: To compare the clinical and functional outcomes associated with open and closed nailing techniques for femoral shaft fractures. Methods and materials: This quasi-experimental study was conducted in the Department of Orthopaedics, Sher-e-Bangla Medical College Hospital, Barisal and Private Hospitals of Barisal from January 2020 to December 2021 over a period of two years. Data analysis was conducted using the Statistical Package for Social Sciences (SPSS), version 12. Results: Mean age was almost similar in both groups. In closed group it was 38.17 ± 10.91 years whereas in open group it was 36.90 ± 11.93 years. In the closed reduction group, RTA accounted for 66.7% of the fractures, followed by falls at 23.3% and physical assault at 10.0%. Similarly, in the open reduction group, RTA was the leading cause at 76.7%, followed by falls at 16.7% and physical assault at 6.7. Union was confirmed maximum in closed cases (93.3%) than open cases (86.7%) but the difference was not statistically significant. Conclusion: It can be concluded that compared to open interlocking nailing techniques, closed interlocking nailing has a number of benefits, including faster union, higher union rates, and a lower infection rate.